2016
DOI: 10.1104/pp.15.01688
|View full text |Cite
|
Sign up to set email alerts
|

A JUMONJI Protein with E3 Ligase and Histone H3 Binding Activities Affects Transposon Silencing in Arabidopsis

Abstract: Transposable elements (TEs) make up a large proportion of eukaryotic genomes. As their mobilization creates genetic variation that threatens genome integrity, TEs are epigenetically silenced through several pathways, and this may spread to neighboring sequences. JUMONJI (JMJ) proteins can function as antisilencing factors and prevent silencing of genes next to TEs. Whether TE silencing is counterbalanced by the activity of antisilencing factors is still unclear. Here, we characterize JMJ24 as a regulator of TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 92 publications
(137 reference statements)
0
16
0
Order By: Relevance
“…Recent studies demonstrated that JMJ25/IBM1 and JMJ27 have histone H3K9 demethylase activity (Saze et al, 2008;Dutta et al, 2017). Although JMJ24 has no demethylase activity in vitro, it can repress H3K9me2 and CHG methylation indirectly at transposons in vivo (Kabelitz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that JMJ25/IBM1 and JMJ27 have histone H3K9 demethylase activity (Saze et al, 2008;Dutta et al, 2017). Although JMJ24 has no demethylase activity in vitro, it can repress H3K9me2 and CHG methylation indirectly at transposons in vivo (Kabelitz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The PHD domains of FGT1 (aa 667–757) and ING1 ( Lee et al, 2009 ) were subcloned into pGEX-4T-1 (Amersham Biosciences, Pittsburgh, PA), expressed in E. coli BL21 (DE3) as GST fusion proteins and purified using Glutathione affinity resins (Thermo Fisher Scientific, Waltham, MA). The histone peptide binding assay was performed as described ( Kabelitz et al, 2016 ). In brief, 1 µg of biotinylated histone peptides (Merck-Millipore, Darmstadt, Germany) were incubated with 10 µg of GST-fusion protein in binding buffer (50 mM Tris-HCl pH 7.5, 300 mM NaCl, 0.1% NP-40, 1 mM PMSF, protease inhibitors) overnight at 4°C with rotation.…”
Section: Methodsmentioning
confidence: 99%
“…After incubation with Streptavidin Dynabeads (Thermo Fisher Scientific) and extensive washing with TBST, bound proteins were analyzed by SDS-PAGE and immunoblotting with anti-GST antibodies (Merck-Millipore). Results for GST-ING1 were taken from Kabelitz et al (2016) , as the experiments were performed in parallel.…”
Section: Methodsmentioning
confidence: 99%
“…DNA methylation and repressive histone marks, H3K9me, are highly correlated with gene silencing (Du et al ., 2015). Recent studies revealed that the RING motif of JMJ24, instead of the JmjC domain that is well characterised with histone demethylase activity (Klose et al ., 2006; Deng et al ., 2016), is required for regulating CHG methylation and H3K9me2, to reinforce transcriptional silencing (Klose et al ., 2006; Deng et al ., 2016; Kabelitz et al ., 2016). Rbx1, the core subunit in SCF complex, contains the RING domain (Gray et al ., 2002; Zheng et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%